2003
DOI: 10.1097/01.sla.0000094442.12395.98
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Intravenous Infusion of Bovine Hemoglobin Significantly Reduces Microcirculatory Dysfunction in Experimentally Induced Pancreatitis in the Rat

Abstract: In severe acute pancreatitis, single i.v. injection of bovine hemoglobin improves pancreatic microcirculation and reduces tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
0
30
0
1
Order By: Relevance
“…In SAP, the production of a large number of cytokines and vasoactive substances can, directly or indirectly, give rise to decreased local blood flow and blood flow velocity, leukocyte adhesion, and increased capillary permeability, which can cause microcirculatory disturbances (Strate et al, 2003;von Dobschuetz et al, 2004). Microcirculatory disturbance is one of the trigger factors for the development of acute pancreatitis (AP) (Foitzik et al, 2000;Qu et al, 2003).…”
mentioning
confidence: 99%
“…In SAP, the production of a large number of cytokines and vasoactive substances can, directly or indirectly, give rise to decreased local blood flow and blood flow velocity, leukocyte adhesion, and increased capillary permeability, which can cause microcirculatory disturbances (Strate et al, 2003;von Dobschuetz et al, 2004). Microcirculatory disturbance is one of the trigger factors for the development of acute pancreatitis (AP) (Foitzik et al, 2000;Qu et al, 2003).…”
mentioning
confidence: 99%
“…In contrast, animal studies have shown improved tissue oxygenation during blood exchange, restoration of the pancreatic microcirculation and tissue oxygen tensions, and reduced acidosis with better mucosal integrity of the intestine after resuscitation from hemorrhagic shock with different HBOC [16,24,25]. In experimental acute pancreatitis bovine HBOC-301 was able to significantly reduce histologic tissue damage in rats [26]. In acute porcine pancreatitis hemodilution with HES plus HBOC-301 improved the pancreatic microcirculation and tissue oxygenation and increased the 6-day survival rate [27].…”
Section: Animal Experiments With Hemoglobin-based Oxygen Carriersmentioning
confidence: 91%
“…Pulmonary gas exchange can possibly be improved with HBOC entering compressed capillaries in zone I of the lung in critically ill patients [55]. Because of the vasopressor properties (NO scavenging) in combination with improved perfusion and oxygen release on the microcirculatory site, HBOC may particularly be useful in the treatment of sepsis and acute pancreatitis [26,27]. Animal experiments of septic shock demonstrated hemodynamic stabilization without significant adverse effects on regional organ blood flow using cell-free Hb [56].…”
Section: Possible Indications Of Hboc In the Futurementioning
confidence: 99%
“…In recent years, some studies have found that, during the development and progression of SAP, the premature activation of pancreatic enzymes in acinar cells and excessive inflammatory reaction can induce the production of a large number of cytokines and vasoactive substances that are able to, directly or indirectly, give rise to the decrease in local blood flow, blood flow velocity, leukocyte adhesion and capillary density as well as the increase in capillary permeability, thereby inducing microcirculation disturbance [8,9]. In turn, microcirculation disturbance is one of the important factors that can induce the production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%